2004
DOI: 10.1016/j.jacc.2003.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 contributes to human atrial remodeling during atrial fibrillation

Abstract: We clearly showed that the expression of the MMP-9 increased in fibrillating atrial tissue, which may have contributed to the atrial structural remodeling and atrial dilatation during AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 38 publications
5
97
1
1
Order By: Relevance
“…It was postulated that activation of different MMPs can modulate extracellular matrix collagen disintegration, which can in turn cause the structural and hence electrical remodelling of human atria. 3,4) It was also proven that Hcy can upregulate the activity of MMPs 2 and 9. 5,6) Another experimental study showed that Hcy could cause electro-physiological disturbances of potassium currents in human atrial myocytes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was postulated that activation of different MMPs can modulate extracellular matrix collagen disintegration, which can in turn cause the structural and hence electrical remodelling of human atria. 3,4) It was also proven that Hcy can upregulate the activity of MMPs 2 and 9. 5,6) Another experimental study showed that Hcy could cause electro-physiological disturbances of potassium currents in human atrial myocytes.…”
Section: Discussionmentioning
confidence: 98%
“…1,2) It has been proven in previous studies that enhanced activity of matrix metalloproteinases (MMPs) may also be one of the mechanisms responsible for this. 3,4) It has been shown in animal studies that metalloproteinases in endocardial cells could be activated by homocysteine (Hcy). 5,6) Elevated levels of Hcy are associated with an increased risk of coronary artery disease and cerebrovascular disease.…”
mentioning
confidence: 99%
“…Remodeling of the atrial extracellular matrix, manifested by selective downregulation of TIMP2 expression and up-regulation of MMP2 expression, has been associated with the development of sustained AF (43). The markedly increased expression of MMP2 in the atria of patients with AF thus suggests the importance of this enzyme not only in extracellular matrix remodeling but also in the development of atrial dilation during progression of AF (43,44). In this study we showed that the -1306C➝T polymorphism of MMP2 is associated with AF, with the T allele representing a risk factor for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,17- 21 We previously demonstrated that MMP-9 expression increases in fibrillating atrial tissue, which may contribute to the atrial structural remodeling of AF. 22 However, the mechanism of the increase in MMP-9 expression in fibrillating atrial tissue remains unknown.…”
Section: Ogi H Et Almentioning
confidence: 99%